Dynamic topology awareness-based reconfigurable service carrying network reconfiguration - Ning-ning LIANG; Ju-long LAN; Zhen ZHANG (Tongxin xuebao)
Reconfigurable information communication basal network supports self-adaptive services to applications by constructing reconfigurable service carrying network(RSCN). To effectively utilize the limited substrate network resources, an algorithm of dynamic topology awareness-based RSCN reconfiguration (DTAR)was proposed. The algorithm uses the number of shortest paths as resource critical degree which across the node or link to distinguish substrate resource. And it also dynamically awares the states of critical resources, reoptimises the RSCN according to service request. Experimental results show that comparing with the existing algorithms, the sed algorithm achieves higher success ratio, gains higher revenue, cost ratio and load equilibrium for substrate network.